Rancang Bangun Robot Selam Mini Berbasis Arduino - Sunardi, Sunardi; Nurtiyanto, Woro Agus; Setiawan, Jan; Abdussalam, Abdussalam (Universitas Pamulang, Prodi teknik Elektro, 2024)
The innovation of submerged or submerged robots is currently prominent enough to be noticed by the general public, the country and even the world. Previously there were still many submerged exercises that were controlled using cable media. In this research, the diving robot controller uses wireless conductive media. Because currently robots can move submerged, it is hoped that they can help human activities. The Submerged Pack robot is an Arduino-based ROV (Remotely Operated Vehicle) which is smaller than usual. This robot uses 4 engines to move and is equipped with a camera and lighting frame to screen submerged conditions. Arduino as the main microcontroller controls the Flysky FS-i6 via a link so that the robot can be controlled from above the water surface. The essence of this examination is to be able to design submerged robots that can replace traditional submerged exercises. The main thing in the scaled-down ROV plan is its control frame and watertight frame. The framework for the observation and lighting system uses lights and is equipped with a camera. The expected results from this diving robot are normal, that the robot can move according to the four commands which can be applied as a prototype for observing diving.